49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3990
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Instability Mechanisms in a Pressure-coupled Gas-gas Coaxial Rocket Injector

Abstract: An investigation of the instability mechanism present in a laboratory rocket combustor is performed using computational fluid dynamics (CFD) simulations. Three cases are considered which show different levels of instability experimentally. Computations reveal three main aspects to the instability mechanism, the timing of the pressure pulses, increased mixing due to the baroclinic torque, and the presence of unsteady tribrachial flame. The stable configuration shows that fuel is able to flow into the combustor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Other important processes included increased mixing due to baroclinic torque which produced vorticity and the presence of a tribrachial flame as a strong source for unsteady heat release. The existence of the tribrachial flame in this combustor was earlier identified by Garby et al 11 Harvazinski et al 16 also noted the complexity of the triple flame dynamics, moving throughout the combustor, with periodic extinction and re-ignition.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Other important processes included increased mixing due to baroclinic torque which produced vorticity and the presence of a tribrachial flame as a strong source for unsteady heat release. The existence of the tribrachial flame in this combustor was earlier identified by Garby et al 11 Harvazinski et al 16 also noted the complexity of the triple flame dynamics, moving throughout the combustor, with periodic extinction and re-ignition.…”
Section: Introductionmentioning
confidence: 89%
“…Three-dimensional simulations of the same single-injector combustor were better able to capture the higher order harmonic modes with limit cycle amplitudes that approached the experimental data. 10,15 Harvazinski et al 16 further identified three influential processes of the instability mechanism. The first process was the timing of pressure pulses between the combustor and oxidizer post.…”
Section: Introductionmentioning
confidence: 97%
“…To further understand the observations as well as to develop strategic knowledge, it is important to complement the experiments with modeling. High fidelity CFD models have shown promise in this regard [27][28][29] . Most of these models, however, utilize global reaction schemes, owing to the significant computational cost and challenges associated with detailed chemical kinetics models.…”
Section: A Detailed Chemistry Modelsmentioning
confidence: 99%
“…High-fidelity CFD simulations of the CVRC geometry have been performed by using a variety of models and codes, a review of which is available in Ref. 4. The majority of the published results have focused on the unstable intermediate post-length cases and, in general, three-dimensional simulations have reproduced amplitudes slightly lower than those observed in the experiment.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, reacting flow computational fluid dynamics (CFD) simulations are starting to be successful in modeling combustion instability in a variety of configurations including gas turbines and rocket engines. [4][5][6][7][8][9][10][11][12][13] The single-element engine chosen for this study is the continuously variable resonance combustor (CVRC) experiment. The CVRC is a gas-gas shear-coax rocket engine configuration that can be tuned to exhibit both stable and unstable combustion regimes.…”
Section: Introductionmentioning
confidence: 99%